(untitled) (Perner’s Contacts, 2011)
The town of Ostrava (the Czech Republic) proposed to build a new public transport terminal for bus traffic in order to improve traffic organization in the locality and to make public transport more attractive for passengers. The project of the new hub expects to build some new constructions (platforms, parking places etc). The aim is to find out if the proposed number of constructions is sufficient for expected number of transport lines and passengers in the transport hub. The computer simulation is used to solve the problem of the hub verification. Two simulation models are created in application called Witness to simulate the traffic in the transport terminal. The simulation methods have proved to be very suitable for verifying quantitative parameters of transport projects. The research found out the delay "a desirable phenomenon” for the number of parking places. The delays reduce their required number.